1965
DOI: 10.1084/jem.122.2.237
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Walls of Group D Streptococci

Abstract: The type-specific carbohydrates of Group D streptococci are components of the cell wall and are the structural and chemical counterparts of the specific carbohydrates of Groups A, B, C, and G streptococci (1). Although a number of serologic types of Group D streptococci have been identified, the immunochemical basis for this antigenic classification has not been elucidated (2) The Group D antigen, unlike the group-specific carbohydrates for most of the other streptococcal groups, is a cytoplasmic constituent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0
1

Year Published

1966
1966
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…However, only limited information is available on the specific role of polysaccharide antigens in the pathogenicity of enterococcal infections (1,2,13,39,40). CP antigens and teichoic acids from enterococci have been identified and partially characterized by a number of investigators in the past (3,4,9,(25)(26)(27), but the host immune response to these antigens and their potential usefulness as vaccines have not previously been elucidated. Only one attempt at a systematic seroepidemiologic approach to classifying enterococci based on CP structures has been reported (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…However, only limited information is available on the specific role of polysaccharide antigens in the pathogenicity of enterococcal infections (1,2,13,39,40). CP antigens and teichoic acids from enterococci have been identified and partially characterized by a number of investigators in the past (3,4,9,(25)(26)(27), but the host immune response to these antigens and their potential usefulness as vaccines have not previously been elucidated. Only one attempt at a systematic seroepidemiologic approach to classifying enterococci based on CP structures has been reported (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…However, we were not able to detect the PS antigen in several E. faecalis strains. Early studies of E. faecalis showed that some cell wall PS were antigenic and might be used for serological typing (1,9,19,21). Neither the chemical compositions nor the genetic basis of these PS have been elucidated.…”
mentioning
confidence: 99%
“…There is very little information available on cell surface-associated polysaccharides of enterococci. Crude cell wall extracts from E. faecalis type 1 strains performed in the 1960s were found to contain L -rhamnose, glucose, galactose, N-acetylglucosamine and N-acetylgalactosamine [34]. More recently, a carbohydrate polymer was identified containing L -rhamnose, glucosamine, galactosamine, glucose, galactose, and phosphate in a 4:2:2:1:1:1 ratio [35].…”
Section: Discussionmentioning
confidence: 99%